Networks at the science-policy-interface: Challenges, opportunities and the viability of the 'network-of-networks' approach. Issue 123 (September 2021) - Kelemen, Eszter; Pataki, György; Konstantinou, Zoi; Varumo, Liisa; Paloniemi, Riikka; Pereira, Tânia R.; Sousa-Pinto, Isabel; Vandewalle, Marie; Young, Juliette
Abstract: An approach that has been suggested as potentially addressing the challenges of science-policy-interfaces (SPIs) is the mobilization of existing networks through a 'network-of-networks' (NoN) approach. This paper shares empirical findings from a mixed-method study, combining qualitative and quantitative data, that critically evaluates the 'network-of-networks' approach for SPIs. To establish whether and how a NoN can help existing networks act more effectively at the boundary of science and policy, we use the Eklipse Mechanism as a key example. We analyse the major characteristics of networks active in biodiversity-focused science-policy interactions, the potential roles and types of engagement of participants, and the major challenges faced by networks and individuals when acting at the boundaries of science and policy. Results suggest that the more diverse the actors involved, the more effective the SPI. While a formalized EU-level SPI for biodiversity is welcomed by most respondents, willingness and actual potential to contribute to such an entity differed amongst networks, highlighting that contributions to SPIs are highly dependent on individual and organizational capacities. The challenges faced by individuals and networks range from limited resources to effective communication and achieving meaningful impact even if the institutional context is unrewarding. To make a 'network-of-networks' model fully operational requires meeting the capacity building needs of networks, providing institutional support, and creating room for wider engagement.